Super athletes or gene cheats? - McCrory, P. (British Journal of Sports Medicine, 2003)
The threat of gene transfer technology to elite sport The International Olympic Committee (IOC) recently released its new list of banned substances and methods. This list will be effective from 1 January 2003 and replaces the 1 September 2001 list. Amongst the important changes, the category of genetic doping as a banned method is listed for the first time. The current list can be easily accessed on both the IOC and World Anti-Doping Agency (WADA) websites (www.wada-ama.org or www.olympic.org)